2021
DOI: 10.18805/lr-4553
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Production of Both Lac and Pulse from Pigeonpea [Cajanus cajan (L) Millsp.] for Doubling Farmers’ Income

Abstract: Background: Pigeonpea [Cajanus cajan (L.) Millsp.] is an important deep-rooted pulse crop, predominantly cultivated in rainfed areas by both Indian and South African countries by small and marginal farmers. Incidentally, this group of farmers are malnourished and socio-economically backward.Methods: A low input technology-‘Jawahar model for doubling income of resource constrained marginal farmers’ was evaluated once again with different combination of soil microbes in a substrate filled in used Polypropylene b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…2023) on lac production on pigeonpea the benefit cost ratio was 1.95 and 2.09 in lac inoculated experiment and it was higher than the sole seed crop (control) of pigeon pea (1.84 and 1.35) in season 2019-20 and 2020-21, respectively. All the studied parameters revealed that pigeon pea was found to be an economically efficient host for lac production [16].…”
Section: Interactions (Spacings X Levels Of Irrigation)mentioning
confidence: 95%
“…2023) on lac production on pigeonpea the benefit cost ratio was 1.95 and 2.09 in lac inoculated experiment and it was higher than the sole seed crop (control) of pigeon pea (1.84 and 1.35) in season 2019-20 and 2020-21, respectively. All the studied parameters revealed that pigeon pea was found to be an economically efficient host for lac production [16].…”
Section: Interactions (Spacings X Levels Of Irrigation)mentioning
confidence: 95%
“…Removal of the left-over brood lac twigs from C. cajan after complete emergence of lac nymphs from female cells is, Phunki removal operation. It was carefully removed from C. cajan plant 21 days after BLI without damaging the freshly settled lac insects on the branches [1], [20].…”
Section: Vii) Phunki Removalmentioning
confidence: 99%
“…Pigeonpea (Cajanus cajan (L.) Millsp) is a deeprooted pulse crop that is mostly grown in rainfed regions by small and marginal farmers in South Africa and India [1]. Interestingly, this group of farmers is undernourished and has a low socioeconomic status [1]. The crop proved to be an effective lac insect host plant.…”
Section: Introductionmentioning
confidence: 99%
“…Its split seeds known as daal in India is widely consumed [6]. This leguminous crop is grown as rainfed crop through the country [7], in an area of 4,550 thousand hectares [6]. The crop is attacked by insect pests which reduces its yield by 15 to 25 percent [8].…”
Section: Introductionmentioning
confidence: 99%
“…Lac is also a cash crop [14][15][16] and therefore plays an important role in the socioeconomy of small and marginal farmers. Thus, both pigeonpea and lac are important crops obtained from the same crop simultaneously [7]. The present study was to explore the performance of C. cajan with different load of lac insects and soil moisture for yield of lac and grain.…”
Section: Introductionmentioning
confidence: 99%